2023
DOI: 10.1101/2023.02.14.528513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dephosphorylation of 4EBP1/2 Induces Prenatal Neural Stem Cell Quiescence

Abstract: A limiting factor in the regenerative capacity of the adult brain is the abundance and proliferative ability of neural stem cells (NSCs). Adult NSCs are derived from a subpopulation of embryonic NSCs that temporarily enter quiescence during mid-gestation and remain quiescent until postnatal reactivation. Here we present evidence that the mechanistic/mammalian target of rapamycin (mTOR) pathway regulates quiescence entry in embryonic NSCs of the developing forebrain. Throughout embryogenesis, two downstream eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…To investigate whether rocaglates from different structural subgroups were bioactive in MV411 leukemia cells and whether this bioactivity extended to healthy cells, we tested an expanded library of 37 rocaglates, intentionally weighted toward known bioactive molecules, with representation from each of the three subclasses at 10 µM on MV411 and healthy peripheral blood mononuclear cells (PBMCs) (Figure 2A). The primary staining panel was selected to test a range of cell functions including cell growth, translation, and death and has been validated in previous work: Ki67 (cell proliferation 45,46 ), phospho-S6 ribosomal protein at serine 240/244 (p-S6 S240/244) (growth, AKT/mTORC1 specific 47,48 ), phosphorylation of gamma H2AX at serine 139 (γH2AX) (DNA damage response 49 ), phosphorylation of STAT3 at serine 727 (p-STAT3) (amplified transcriptional activity, downstream mTOR 50 ), phosphorylation of STAT5 at tyrosine 694 (p-STAT5) (cell survival, highly phosphorylated in cancer cells 51,52 ), phospho-S6 ribosomal protein at serine 235/236 (p-S6 235/236) (growth, activated by ERK/RSK and AKT/mTORC1 47,48 ), phosphorylation of ERK1/ERK2 at threonine 202, tyrosine 204 (p-ERK1/2) (proliferation, activated by MAP kinase cascade 53,54 ), phosphorylated histone H3 at serine 28 (p-HH3) (growth, cell cycle M phase 55 ), phosphorylation of 4EBP1 at threonine 37/46 (p-4EBP1) (growth, activated by mTORC1 56 ), phosphorylation of lymphocyte-specific protein tyrosine kinase at tyrosine 505 (p-LCK) (SRC-family kinase involved in T-cell receptor signaling 57 ), and phosphorylation of Akt at serine 473 (p-Akt) (Upstream of mTOR 41,58 ) (Supplementary Table 1) 59,44,60 .…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether rocaglates from different structural subgroups were bioactive in MV411 leukemia cells and whether this bioactivity extended to healthy cells, we tested an expanded library of 37 rocaglates, intentionally weighted toward known bioactive molecules, with representation from each of the three subclasses at 10 µM on MV411 and healthy peripheral blood mononuclear cells (PBMCs) (Figure 2A). The primary staining panel was selected to test a range of cell functions including cell growth, translation, and death and has been validated in previous work: Ki67 (cell proliferation 45,46 ), phospho-S6 ribosomal protein at serine 240/244 (p-S6 S240/244) (growth, AKT/mTORC1 specific 47,48 ), phosphorylation of gamma H2AX at serine 139 (γH2AX) (DNA damage response 49 ), phosphorylation of STAT3 at serine 727 (p-STAT3) (amplified transcriptional activity, downstream mTOR 50 ), phosphorylation of STAT5 at tyrosine 694 (p-STAT5) (cell survival, highly phosphorylated in cancer cells 51,52 ), phospho-S6 ribosomal protein at serine 235/236 (p-S6 235/236) (growth, activated by ERK/RSK and AKT/mTORC1 47,48 ), phosphorylation of ERK1/ERK2 at threonine 202, tyrosine 204 (p-ERK1/2) (proliferation, activated by MAP kinase cascade 53,54 ), phosphorylated histone H3 at serine 28 (p-HH3) (growth, cell cycle M phase 55 ), phosphorylation of 4EBP1 at threonine 37/46 (p-4EBP1) (growth, activated by mTORC1 56 ), phosphorylation of lymphocyte-specific protein tyrosine kinase at tyrosine 505 (p-LCK) (SRC-family kinase involved in T-cell receptor signaling 57 ), and phosphorylation of Akt at serine 473 (p-Akt) (Upstream of mTOR 41,58 ) (Supplementary Table 1) 59,44,60 .…”
Section: Resultsmentioning
confidence: 99%
“…The uncoupling of p-4EBP and p-RPS6 has already been documented in neurogenesis. For example, while p-4EBP marks neural stem cells undergoing mitosis and NPCs at the ventricular surface, p-RPS6 marks more differentiated cells migrating away from the ventricle ( 9 , 42 , 43 ). Interestingly, it was shown that NPCs marked with p-4EBP had higher levels of ribosomal protein mRNAs compared with more mature neurons marked with p-RPS6, but the difference was buffered at the level of translation in cortical brain organoids ( 43 ).…”
Section: Discussionmentioning
confidence: 99%